The Orientalism of Arabs in Larry Charles Film’s The Dictator - Iyank Zona Brammastian (Universitas Sebelas Maret, 2019)
This article aims to portray the Orientalism of Arabs in Larry Charles’s film The Dictator (2012). The research applies Edward Said’s Orientalism to define the Western perspective in representing the awful images of Arabs in the film. It also deploys post-colonial discourse and comedy film theory in defining the distorted images of Arabs which often represented not as its natural form in this comedy genre film. As the result – throughout many Western and Orientalist creations – Arabs are depicted as bomber, barbaric and lustful.